Web crippling design of channel beams: Carbon steel, stainless steel and aluminium. (September 2022) - McIntosh, Alex; Kanthasamy, Elilarasi; Poologanathan, Keerthan; Gunalan, Shanmuganathan; Gatheeshgar, Perampalam; Corradi, Marco; Higgins, Craig
Abstract: Recent trends in the construction industry have sought to use cold-formed (CF) carbon steel, CF aluminium and CF stainless-steel as flexural members and in some instances as primary load-carrying members. Flexural members when subjected to concentrated loads undergo various failure modes, a major failure mode being web crippling. The large width-to-thickness ratios of these thin-walled beams makes them vulnerable to local buckling failure. Although there are four loading conditions to consider, this paper focuses on Interior-One-Flange (IOF) loading condition. Currently, individual design equations are available for determining the web crippling capacity of CF carbon steel, CF aluminium and CF stainless-steel under IOF loading. However, to-date there has been no attempt to produce a unified web crippling design equation. An all-encompassing numerical study focussed on the key web crippling parameters, both cross-sectional dimensions and mechanical properties and a unified grade, fy = 220 MPa, was achieved across the three structural materials to allow for a unified design equation. A total of 378 Finite Element (FE) models were obtained. It was found that AS/NZS 4600, AISI S100 and Eurocode 3 provided good agreement, but with a higher coefficient of variation (COV) values than recommended. Additionally, AS/NZS 1664.1 was found to be unsafe. CF carbon steel parametric study results validated existing equations, which were accurate and able to predict the web crippling capacity under IOF loading. However, unified web crippling design equation was modified which can improve the accuracy when predicting the web crippling capacity of CF aluminium and CF stainless-steel lipped channel sections (LCBs) under IOF loading conditions. The unified equation was supplemented by web crippling coefficients specific to each of the structural materials. Highlights: Web crippling behaviour of lipped channel section was investigated for cold-formed carbon, aluminium and stainless steel Finite element models using Abaqus were generated and validated with IOF experimental data set Parametric study was conducted for three materials: cold-formed carbon steel, aluminium and stainless steel Proposed coefficients to unified web crippling design equation considering yield strength and elastic modulus factors Accuracy of the proposed equations for all three materials were calculated and listed